Análise do índice de desvantagem vocal e a presença de distúrbio de voz em docentes - Queiroz, Daniela Ramos de (2011)
Scientific publications in professional voice have grown in recent years and, among them, teachers are the most searched. The completed self-referential speech help to define behaviors for preventing voice disorders in relation to improving the quality of life and work of a professional voice. Objective: To assess the association between the Vocal Handicap Index (VHI) in teachers with and without voice disorder, diagnosed by means of perceptual auditory and visual. Method: All 354teacherswho participated in the study responded to the questionnaires Vocal Handicap Index(VHI) and Condition of Vocal Production -Teacher (CPV-P), and have been submitted to a Speech Therapist evaluation and otorhinolaringologist to identify possible voice disorder. For statistical analysis, results were analyzed using Chi-square and Kruskal-Wallis test. Results: For the CPV-P, the results show statistical significance for the data "number of schools where she teaches" (p =0.008)and "professional time" (p =0.048). All areas of VHI showed significant results when comparing the mean of each domain and focus group research. Conclusion: In this study, teachers who had vocal disorder, diagnosed by the perceptual evaluation, and /or visual had higher percentages in relation to responses to VHI, indicating greater impact of disadvantage vocal in their day-to-day